TSSpredator-Web: A web-application for transcription start site prediction and exploration - Mathias Witte Paz; Alexander Herbig; Kay Nieselt (PLoS ONE, 2026)
Background With the rapid development of high-throughput RNA-seq technologies, the transcriptome of prokaryotes can now be studied in unprecedented detail. Transcription start site (TSS) identification provides critical insights into transcriptional regulation. Still, current command-line tools for the prediction of TSS remain challenging with respect to their usability and lack of integrated exploration features. Results We introduce TSS predator -W eb , an interactive web application that enhances the usability of the established yet unpublished tool, TSS predator . TSS predator -W eb facilitates TSS prediction from non-enriched and enriched RNA-seq data, classifies TSS relative to annotated genes, and allows users to explore results through dynamic visualizations and interactive tables. For the visualizations, we provide an UpSet plot summarizing the TSS distribution across experiments or classes, and a genome viewer that integrates transcriptomic and genomic data, which contextualizes the insights of the TSS predictions. To illustrate the usage of TSS predator -W eb , we provide a use case with Cappable-seq data from Escherichia coli . TSS predator -W eb is available on the TueVis visualization web-server at https://tsspredator-tuevis.cs.uni-tuebingen.de/ . Conclusions By combining user-friendly accessibility with interactive data exploration, TSS predator -W eb significantly facilitates genome-wide TSS analysis and interpretation in prokaryotes, empowering a broader range of researchers to generate biological insights from transcriptomic data.